Amino Acids Isolation from α-keratin of Javanese Goat (Capra hircus) Hair and Garut Sheep (Ovis aries) Hair Waste Using Acid Hydrolysis Method as BCAA Supplement - Firdaus, Dzikri Anfasa; Andrianto, Dimas; Darmawan, Noviyan (Jurnal Kimia Valensi, 2024)
Javanese goat and Garut sheep hair contain α-keratin, a protein that can be broken by hydrolysis to produce simpler amino acids. Feather waste generates millions of tons of α-keratin biomass originating from animal slaughterhouses, thereby raising health concerns. The utilization of acid hydrolysis is considered to be more cost-effective compared to enzymatic hydrolysis, and it provides a broader range of amino acid cleavage sites compared to enzymes, which exhibit specific cleavage. This study aimed to isolate amino acids from Javanese goat and Garut sheep hair through acid hydrolysis. The methods included hair sample preparation, acid hydrolysis used 6 M HCL at 110°C, reflux isolation, amino acid separation based on isoelectric pH 4.9 –5.4, functional groups analysis using FTIR, and analysis of amino acid content by HPLC methods. The results showed that the yield produced after isolation on Javanese goat hair samples was 0.92% and Garut sheep hair 0.32%, respectively. The FTIR spectrum showed amino acid functional groups in both samples, including carboxyl (COOH), amine (C-N primer), (C-S disulfide), and amide I (-CONH2). Successful breakdown of α-keratin proteins into simpler amino acids was achieved for Javanese goat and Garut sheep hair. Amino acid analysis of Javanese goat hair isolates revealed the presence of aspartic acid, threonine, serine, glutamate, proline, glycine, alanine, valine, methionine, isoleucine, leucine, tyrosine, phenylalanine, histidine, lysine, and arginine amino acids, respectively. The highest content was isoleucine at 0.60% w/w. In conclusion, the isolated amino acids from Javanese goat hair can be used as a halal supplement that serves as nutrition in the body.